Implementation of Cash Social Assistance Program (BST) During The Covid-19 Pandemic In Tabalong Regency, Indonesia - Rizky Kurniadi Wijaya; Andi Tenri Sompa; Siswanto Rawali (International Journal of Politic, Public Policy and Environmental Issues, 2022)
The Cash Social Assistance Program (BST) is one of the aid programmes for victims of the Covid-19 pandemic. It gives money to low-income, vulnerable, and low-income families. BST is the only programme that provides social protection to the village's residents. It differs from the autonomous village in that it can assist the community in a wider variety of ways and with greater flexibility. This is because Kelurahan and Desa are located in separate locations. This study employs a descriptive methodology for qualitative research. Interviews, observation, and documentation are methods for collecting data. People who assisted with the research included the head of Social Service, the Sub-District of Murung Pudak, the Village Head of Mabu'un, the head of the Post Office in Murung Pudak, Social Welfare workers from the Murung Pudak District, the Village Facilitator of Mabu'un, the head of RT Mabu'un Village, and beneficiaries of the programme. Data reduction, data presentation, and conclusion were utilised for data analysis. The results of the research on implementing cash social assistance in Mabu'un Village indicate that, in general, everyone is aware of what's going on, as each stakeholder has performed his or her specific function. This is supported by the fact that good people are committed, trustworthy, and loyal to implementing the BST Program despite the absence of special incentives. Obstacles to the BST Program include overlapping beneficiary data, unclear criteria, a community mentality that is always dependent on the government, a lack of public understanding of the types of assistance, immigrants in Mabu'un village in Population Administration not knowing about the BST Program, so they do not enrol, and a lack of staff to distribute BST disbursement invitations.